MENINGKATKAN KEMAMPUAN SPASIAL SISWA MELALUI PEMBELAJARAN GEOMETRI BERBANTUAN CABRI 3D - Yanty Putri Nasution, Eline (Universitas Wiralodra, 2017)
The purpose of this study are to investigate and to describe the gain of students‘ spatial ability through Geometry teaching and learning by using a dynamic geometry software, Cabri 3D. This study was a quasi experimental research with not equivalent control group design. Direct instruction was implemented in control group otherwise Geometry teaching and learning with using Cabri 3D was implemented in experimental group. The population of this study are all of the eight grade of junior high school students in one of the SMP Negeri in Padangsidimpuan City. The sample of this study were two groups of eighth grade. The sample has been choosed with using purposif sample technique. The instruments of this study were spatial ability test, quationere, observation sheet and interview. The test was analysed quantitatively and non test was analyzed qualitatively in order to answer the the hypotesa, the gain of students’ spatial ability who has studied and lerant with using Cabri 3D is better than direct instruction.